Manajemen Program Ekstrakurikuler untuk Meningkatkan Kegiatan Prestasi Non-Akademik Siswa di MAN 3 Cirebon - Faizal Amir (Eduvis : Jurnal Manajemen Pendidikan Islam, 2021)
The development of extracurricular activities which are part of self-development at school is very important. In addition to many schools that are known to the public because of their achievements in the academic field, there are not a few schools that are chosen by the community because they have achievements in non-academic fields, including through extracurricular activities. To be able to improve extracurricular achievements from students, management is needed as a party for education. MAN 3 Cirebon has a number of achievements in the field of extracurricular activities and won both district and provincial levels. Based on the background above, the authors conducted the study with the aim of revealing how the management of extracurricular programs to improve students' non-academic achievements in Cirebon 3 MAN, with the aim of research: (a) To know the extracurricular activities program planning to improve student non-academic achievements MAN 3 Cirebon. (b) To study and describe the implementation of extracurricular activities programs to improve students' non-academic achievements in Cirebon 3 MAN. (c) Review and describe in more depth the program evaluation of extracurricular activities to improve students' non-academic achievements in MAN 3 Cirebon. (d) Describe the implications of the extracurricular activities program for improving non-academic achievements of students in Cirebon 3 MAN. The research approach itself uses a qualitative approach, namely research that intends to understand the phenomenon of what is experienced by research subjects, for example: behavior, perception, motivation, action, and others, in a holistic manner. Data collection is done by observation, documentation, and interview techniques. . Data analysis techniques include data reduction, data presentation, and conclusion drawing. The conclusion of this study is that the planning implemented in Cirebon 3 MAN will form extracurricular activities that aim to facilitate students in sharpening their interests and talents according to their respective fields of expertise. The implementation of the extracurricular program in MAN 3 Cirebon includes the main tasks carried out by the supervisor, the general task of the coach is to foster students in MAN 3 Cirebon in a variety of continuous and continuous extracurricular activities so that they have qualified abilities and skills. After that the students are selected by the coach and sent to take part in various competitions representing the school and deliver to the destination if the activity is carried out outside the school environment, such as competitions, shows and trips. The evaluation process carried out by determining the extent to which educational goals can be achieved through written test and practice will be followed by an extracurricular team coordination meeting, where principals and parties involved in extracurricular activities such as student affairs and curriculum as well as extracurricular advisors discuss developments and the obstacles faced during the implementation of extracurricular activities and solving the solution. To be repaired in the next semester. The implication of this research is that increasing non-academic achievement of students through extracurricular programs includes: training discipline, training students' talents, and schools being known to the wider community. Abstrak Perkembangan kegiatan ekstrakurikuler yang merupakan bagian daripengembangan diri di sekolah menjadi suatu hal yang sangat penting. Selain banyak sekolah yang dikenal masyarakat karena prestasi di bidang akademik, tidak sedikit pula sekolah yang menjadi pilihan masyarakat karena memiliki prestasi di bidang non-akademik, diantaranya melalui kegiatan ekstrakurikuler. Untuk dapat meningkatkan prestasi ekstrakurikuler dari peserta didik maka sebagai pihak kependidikan dibutuhkan suatu manajemen. MAN 3 Cirebon memiliki sejumlah prestasi dalam bidang ekstrakurikuler dan menjadi juara baik tingkat kabupaten maupun propinsi. Berdasarkan latar belakang di atas, penulis melakukan penelitian dengan tujuan untuk mengungkapkan bagaimana manajemen program ekstrakurikuler untuk meningkatkan prestasi non-akademik siswa di MAN 3 Cirebon, dengan tujuan penelitian: (a) Untuk mengetahui perencanaan program kegiatan ekstrakurikuler untuk meningkatkan prestasi non-akademik siswa di MAN 3 Cirebon. (b) Untuk mengkaji dan mendeskripsikan pelaksanaan program kegiatan ekstrakurikuler untuk meningkatkan prestasi non-akademik siswa di MAN 3 Cirebon. (c) Mengkaji dan mendeskripsikan secara lebih mendalam terhadap evaluasi program kegiatan ekstrakurikuler untuk meningkatkan prestasi non-akademik siswa di MAN 3 cirebon. (d) Mendeskripsikan implikasi program kegiatan ekstrakurikuler terhadap peningkatan prestasi non-akademik siswa di MAN 3 Cirebon. Pendekatan penelitian ini sendiri menggunakan pendekatan kualitatif, yaitu penelitian yang bermaksud untuk memahami fenomena tentang apa yang dialami oleh subjek penelitian misalnya: perilaku, persepsi, motivasi, tindakan, dan lainnya, secara holistik.. Pengumpulan data dilakukan dengan teknik observasi, dokumentasi,dan wawancara. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Kesimpulan dari penelitian ini adalah Perencanaan yang diterapkan di MAN 3 Cirebon akan membentuk kegiatan ekstrakurikuler yang bertujuan untuk memudahkan para siswa dalam mengasah minat dan bakatnya sesuai bidang keahliannya masing-masing. Pelaksanaan program ekstrajurikuler di MAN 3 Cirebon meliputi tugas-tugas utama yang dilakukan oleh pembina, tugas umum dari pembina yaitu membina iswa-siswa di MAN 3 Cirebon dalam berbagai kegiatan ekstrakurikuler secara terus-menerus dan berkelanjutan agar mereka memiliki kemampuan dan ketrampilan yang mumpuni. Setelah itu peserta didik di seleksi oleh pembina dan dikirim untuk mengikuti berbagai kompetisi mewakili sekolah dan mengantar ke tujuan apabila aktivitas dilakukan di luar lingkungan sekolah, seperti pertandingan-pertandingan, pertunjukkan-pertujukkan, dan perjalanan. Proses evaluasi yang dilakukan dengan cara menentukan sampai sejauh mana tujuan pendidikan dapat dicapai melalui proses tes tulis dan praktek akan dilanjutkan rapat koordinasi tim ekstrakurikuler, dimana kepala sekolah dan pihak-pihak yang terlibat dalam kegiatan ekstrakurikuler seperti waka kesiswaan dan kurikulum serta para pembina ekstrakurikuler membahas perkembangan dan kendala yang dihadapi selama pelaksanaan kegiatan ekstrakurikuler dan memecahkan solusinya. Untuk dilakukan perbaikan pada semester depan. Implikas dari